Utilizing MRI, [18F]FDG-PET and [89Zr]Zr-DFO-28H1 FAP-PET tracer to assess inflammation and fibrogenesis in a reproducible lung injury rat model: a multimodal imaging study - Boswinkel, Milou; Raavé, René; Veltien, Andor; Scheenen, Tom WJ; Fransén Petterson, Nina; in ‘t Zandt, René; Olsson, Lars E.; von Wachenfeldt, Karin; Heskamp, Sandra; Mahmutovic Persson, Irma (Frontiers in Nuclear Medicine, 2023)
Accurate imaging biomarkers that indicate disease progression at an early stage are highly important to enable timely mitigation of symptoms in progressive lung disease. In this context, reproducible experimental models and read-outs are key. Here, we aim to show reproducibility of a lung injury rat model, by inducing disease and assessing disease progression by multi-modal non-invasive imaging techniques at two different research sites. Furthermore, we evaluated the potential of fibroblast activating protein (FAP) as an imaging biomarker in early stage of lung fibrosis. Methods: An initial lung injury rat model was set-up at one research site (Lund University, Lund, Sweden), and repeated at a second site (Radboudumc, Nijmegen, The Netherlands). To induce lung injury, Sprague-Dawley rats received intratracheal instillation of bleomycin as one single dose (1000iU in 200µL) or saline as control. Thereafter, longitudinal images were acquired to track inflammation in the lungs, at 1 week and 2 weeks post bleomycin challenge by MRI and [18F]FDG-PET. After the final [18F]FDG-PET scan, rats received intravenous tracer [89Zr]Zr-DFO-28H1 (anti-FAP antibody) and were imaged at day 15, to track fibrogenesis. At termination, broncho-alveolar lavage (BAL) was performed to assess cell and protein concentration. Subsequently, biodistribution of [89Zr]Zr-DFO-28H1 was measured ex vivo and the spatial distribution in lung tissue was studied by autoradiography. Lung sections were stained and fibrosis assessed using the modified Ashcroft score. Results: Bleomycin-challenged rats showed body weight loss and increased immune cell numbers and protein concentration in BAL, compared with control animals. Disease initiation and progression were reproduced at both research sites. Lung lesions in bleomycin-exposed rats were visualized by MRI and confirmed by histology. [18F]FDG uptake was higher in lungs of bleomycin-challenged rats compared with controls, similarly as observed in the Lund study. [89Zr]Zr-DFO-28H1 tracer uptake in the lung was increased in bleomycin-challenged rats compared with control rats (p=0.03). Conclusion: Here we demonstrate a reproducible lung injury model and monitored disease progression using conventional imaging biomarkers MRI and [18F]FDG-PET. Furthermore, we showed first proof-of-concept of FAP imaging. This reproducible- and robust animal model and imaging experimental set-up allows for future research on new therapeutics or biomarkers in lung disease.